A facile synthesis methodology for preparation of Ag–Ni-reduced graphene oxide: a magnetically separable versatile nanocatalyst for multiple organic reactions and density functional study of its electronic structures. Issue 66 (12th November 2018) - Chandel, Madhurya; Makkar, Priyanka; Ghosh, Barun Kumar; Moitra, Debabrata; Ghosh, Narendra Nath
Abstract : Here, we report a simple ' in situ ' co-precipitation reduction synthesis method for the preparation of nanocatalysts composed of Ag, Ni nanoparticles, and reduced graphene oxide (RGO). Abstract : Here, we report a simple ' in situ ' co-precipitation reduction synthesis method for the preparation of nanocatalysts composed of Ag, Ni nanoparticles, and reduced graphene oxide (RGO). First-principles calculations based on Density Functional Theory (DFT) were performed to obtain the electronic structures and properties of Ag–Ni-graphene superlattice and to understand the interfacial interactions which exist at the interface between Ag, Ni, and graphene. The catalytic performance of the synthesized catalysts (Ag x Ni(1− x ) ) y RGO(100− y ) were evaluated for four reactions (i) reduction of 4-nitrophenol (4-NP) in the presence of excess NaBH4 in aqueous medium, (ii) A3 coupling reaction for the synthesis of propargylamines, (iii) epoxidation of styrene, and (iv) 'Click reaction' for the synthesis of 1, 2, 3-triazole derivatives. For all of these reactions the catalyst composed of Ag, Ni, and RGO, exhibited significantly higher catalytic activity than that of pure Ag, Ni, and RGO. Moreover, an easy magnetic recovery of this catalyst from the reaction mixture after completion of the catalytic reactions and the good reusability of the recovered catalyst is also reported here. To the best of our knowledge, this is the first time the demonstration of the versatile catalytic activity of (Ag x Ni(1− x ) ) y RGO(100− y ) towards multiple reactions, and the DFT study of its electronic structure have been reported.